Non-matrix-matched calibration of Mg isotopic ratios in silicate samples by fs-LA-MC-ICP-MS with low mass resolution under wet plasma conditions. Issue 3 (21st February 2022) - Lin, Jie; Liu, Yongsheng; Yang, Ao; Chen, Wei; Zhu, Lvyun; Hu, Zhaochu
Abstract : Accurate and precise Mg isotopic analysis by fs-LA-MC-ICP-MS can be performed with low mass resolution and non-matrix-matched calibration. Abstract : In situ Mg isotope analysis of geological materials by laser ablation multiple collector-inductively coupled plasma mass spectrometry (LA-MC-ICP-MS) is a powerful tracer technique for tracking geological processes. In Mg isotopic analysis by LA-MC-ICP-MS, medium or high mass resolution was commonly applied to avoid spectral interferences. However, the improved mass resolution can result in reduced intensity and an aggravated matrix effect. In this study, the analytical results demonstrated that the main interferences ( 12 C 14 N + and 48 Ca 2+ ) in Mg isotopic analysis can be significantly suppressed, and the matrix effect can be significantly reduced with water added after the laser ablation cell ( i.e., wet condition or wet plasma) using fs-LA-MC-ICP-MS. Thus, accurate and precise Mg isotopic composition can be achieved with low mass resolution and the non-matrix-matched calibration method by fs-LA-MC-ICP-MS. The applicability of the combination of low mass resolution and wet plasma was systematically evaluated by the assessment of the interferences, the Mg three-isotope plot, instrumental long-term reproducibility and the intensity mismatch effect. Applying the optimized method, accurate and precise Mg isotopic compositions in silicate reference materials with various matrices can be achieved.